2015
DOI: 10.1007/s11121-015-0625-0
|View full text |Cite
|
Sign up to set email alerts
|

The Outcomes of an Alcohol Prevention Program on Parents’ Rule Setting and Self-efficacy: a Bidirectional Model

Abstract: Most adolescents have their first encounter with alcohol in early or middle adolescence. Parents' rule setting about alcohol has been shown to be important to delay the onset and reduce the frequency of adolescents' alcohol drinking, but less is known about the potential role of parents' beliefs about their competence in and ability to influence their adolescents' drinking habits (i.e., parental self-efficacy [PSE], Bandura (Psychological Review, 84, 191-215, 1977). In this study, we examined the direction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
0
21
0
Order By: Relevance
“…Glatz and Koning’s (2015) recent experimental intervention study assessed the efficacy of enhancing parent competence for preventing adolescent drinking habits. Their intervention was designed to alter positive parental perceptions of self-efficacy via concrete household guidelines and rule setting.…”
Section: Resultsmentioning
confidence: 99%
“…Glatz and Koning’s (2015) recent experimental intervention study assessed the efficacy of enhancing parent competence for preventing adolescent drinking habits. Their intervention was designed to alter positive parental perceptions of self-efficacy via concrete household guidelines and rule setting.…”
Section: Resultsmentioning
confidence: 99%
“…As parenting factors revealed strong relationships with both self-image and one’s peer group for 8th and 10th graders, parent-targeted interventions would seem a worthwhile endeavor for preventing alcohol use by younger adolescents. Building on previous research (Gottfredson and Hussong 2011; Pilgrim et al 2006; Siegel et al 2015), interventions focused on increasing parental involvement in their child’s school and personal life, with an added emphasis on enhancing parent-child alcohol communication (Glatz and Koning 2016), could enhance youth’s self-esteem and decrease their likelihood of associating with deviant peers and reduce the incidence of alcohol initiation. Previous efforts have found that addressing parents (vs. children) in persuasive attempts resulted in less resistance and greater message acceptance by adolescents (Crano et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding parental self-efficacy will be collected by a 3-item scale measuring parents’ confidence in their ability to prevent their adolescent from drinking alcohol, in which higher scores indicate a greater sense of self-efficacy [41]; this has been used and validated in the past PAS studies [42,43]. …”
Section: Methodsmentioning
confidence: 99%
“…Students will also be asked to complete the Kessler 6 scale [47] to assess psychological distress in the past 30 days, and their quality of life will be measured by the Child Health Utility 9D scale [48]. Finally, students’ self-control will be measured using a 13-item scale developed by Tangney et al [49], which was used in the PAS program [32,33,42] and which includes questions such as “I am good at resisting temptation , ” in which students would be asked to indicate how they typically are on a 5-point scale from “Not at all” to “Very Much.” These additional measures will be assessed at baseline and 12- and 24-month follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation